A study of the click beetles (Coleoptera: Elateridae) of northwestern Iran with three new species Reitterelater prosternalis sp. n., Melanotus borumandi sp. n. and M. kurdestanicus sp. n. - Nasserzadeh, Hiva; Platia, Giuseppe (Zootaxa, 2021)
More than 800 specimens collected during 2015–2018 are studied from northwestern Iran. Thirty four species belonging to five subfamilies and 21 genera are listed. Reitterelater prosternalis sp. n., Melanotus borumandi sp. n. and M. kurdestanicus sp. n. are described. The genus Reitterelater and the species Pristilophus melancholicus (Fabricius) are recorded for the first time from Iran. Distributional map and climate data are presented for each species.